Pengaruh Pekerja Anak Terhadap Gejala Putus Sekolah Pada Suku Kajang Ammatoa - Yulia, Irma; Nurlela, Nurlela; Sumilih, Dimas Ario (Universitas Muhammadiyah Makassar, 2026)
Abstract. This study aims to determine the influence of child labor on the school dropout rate among the Kajang Ammatoa tribe and to analyze the extent to which socio-cultural, economic, and educational access factors moderate the relationship between child labor and school dropout rates. This research employs a quantitative approach with an associative research design. The study population consists of 50 individuals divided into five categories: school dropouts, working children who are still in school, parents, traditional leaders, and teachers or school representatives. The sample was determined using a purposive sampling technique, resulting in 44 respondents. Data were collected through questionnaires and documentation, and analyzed using simple linear regression, moderated regression analysis (MRA), t-test (partial), and f-test (simultaneous) with the assistance of SPSS version 26. The results show that, partially, child labor has a significant effect on school dropout rates among the Kajang Ammatoa community. However, simultaneously, the combined influence of child labor with socio-cultural, economic, and educational access factors is not significant in increasing school dropout rates. Keywords : Child Labor, School Dropout, Socio-Cultural Factors, Economy, Educational Access.